From a horizontal mediation to a vertical mediation in the old figurative expressions of northern Africa - (:unkn) unknown (My University, 2018)
Judging by the figurative themes developed from the late Paleolithic to Islamization in the graphic and plastic expressions of northern Africa, beliefs were played out essentially horizontally before the development of agriculture made them take a vertical swing.
Keywords: African Research